Cover and Table of Content - Wijaya, I Made Saka (Jurnal Biologi Udayana; Vol 26 No 2 (2022): JURNAL BIOLOGI UDAYANA, 2022)
Cover and table of content for Jurnal Biologi Udayana volume 26 issue 2 year 2022